Programa educativo de comunicación asertiva para el mejoramiento de la empatía en directivos y docentes nivel primaria del Colegio Cooperativo César Vallejo Iquitos 2023 - Carrasco Chuje, Estefany (2024)
The research posed the question: What is the effect of the assertive communication educational program on improving empathy among primary level directors and teachers at Colegio Cooperativo César Vallejo Iquitos 2023? The primary goal was to evaluate the impact on empathy levels, broken down into cognitive, emotional, and empathic interest dimensions, following the implementation of the mentioned program. To this end, a field, bivariate, and longitudinal research methodology was employed, with an explanatory approach to delve into the causes and effects of the intervention. The study population included 38 directors and teachers from the institution, selected through intentional sampling. Data collection was carried out using instruments validated by specialists, applying pretest and posttest assessments to measure empathy levels. The study's results show a significant increase in general empathy and its specific dimensions after participating in the assertive communication program. The average general empathy experienced a notable growth from 6.91 to 15.50, reflecting a substantial improvement in the participants' empathic capacity. Similarly, significant increases were recorded in the dimensions of cognitive empathy (from 6.92 to 15.05), emotional empathy (from 6.66 to 15.63), and empathic interest (from 7.16 to 15.82), highlighting the program's effectiveness in strengthening such empathic skills.